Essentials of organizational behavior - Robbins, Stephen P. (Prentice Hall, 2000)
Essentials of Organizational Behavior, Sixth Edition provides a reality-based review of organizational behavior in an abbreviated format. Stephen P. Robbins integrates timely topics throughout the book, such as diversity, globalization, and ethics